SOSIALISASI PENERAPAN AKUNTANSI INDUSTRI KECIL MENENGAH (IKM) YANG MEMANFAATKAN SUMBERDAYA LINGKUNGAN DI PULAU TIDUNG SEBAGAI PROSPEK BISNIS: Socialization of the Application of Accounting for Small and Medium Industries (IKM) That Utilize Environmental Resources on Tidung Island as a Business Prospect - Djunaidy , Djunaidy; Rahmadi, ZaraTania; Dharma , Dias Adi; Utomo, Kabul Wahyu; Rizqi , Az-Zahroh (PUAN INDONESIA, 2024)
This dedication is based on observations that show that the application of accounting practices can play an important role in the success or failure of a business. On Tidung Island, there are many small and medium industrial business actors (IKM) who depend on natural resources, especially the fisheries sector, for their survival and livelihood and produce fishery products which are sold in local markets and support the rapidly growing tourism sector, but the application of accounting for SMEs is still weak, even though this application is an effective solution for developing a sustainable business model. To answer this, socialization was held on the application of accounting for small and medium industries (IKM) which utilizes environmental resources on Tidung Island as a business prospect using socialization methods and discussion forums so that solutions to problems can be found such as increasing understanding of Accounting for SME participants on Tidung Island, understanding and being able to practicing basic technology for SME entrepreneurs to utilize the tools that are available and showing the positive impact of implementing accounting on business and environmental sustainability, and how this can support long-term business resilience.